2015
DOI: 10.1038/nutd.2015.3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the gut microbiota of people in France and Saudi Arabia

Abstract: Background/Objectives:The gut microbiota contributes to energy acquisition from food, and changes in the gut microbiome are associated with obesity. The eating habits of Saudis are much different than those of Europeans, and our objective was to compare the fecal microbiota of obese and normal weight Saudis and French.Subjects/Methods:Illumina MiSeq deep sequencing was used to test the gut microbiota of 9 normal weight and 9 obese individuals from Saudi Arabia and 16 normal weight and 12 obese individuals from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
97
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(109 citation statements)
references
References 48 publications
9
97
2
1
Order By: Relevance
“…To obtain high-quality sequences, the raw sequences were filtered and trimmed as previously reported646566. Then, sequences were clustered into operational taxonomic units (OTUs) with a distance limit of 0.03 (equivalent to 97% similarity) using the Usearch software (version 7.1 http://drive5.com/uparse/).…”
Section: Methodsmentioning
confidence: 99%
“…To obtain high-quality sequences, the raw sequences were filtered and trimmed as previously reported646566. Then, sequences were clustered into operational taxonomic units (OTUs) with a distance limit of 0.03 (equivalent to 97% similarity) using the Usearch software (version 7.1 http://drive5.com/uparse/).…”
Section: Methodsmentioning
confidence: 99%
“…24,25 In the present study, we found a high relation of Firmicutes/Bacteroidetes in obese children which is consistent with other studies. 7,[26][27][28] These controversial results could be explained by lifestyles, ethnic groups, 29,30 geographic origin 23 and even by the different experimental, bioinformatics and cohort selection methodologies used. 31 Diet is considered a trigger of intestinal microbiota diversity by altering the gut microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…The primer set was developed by Illumina (FwOvAd_341F 5'TCGTCGGCAGCGTCAGATGTGTA TAAGAGACAGCCTACGGGNGGCWGCAG) and (ReOvAd_785R 5'GTCTCGTGGGCTCGGAGATGTGTATAAGAGACAGGACTA CHVGGGTATCTAATCC). 69 PCRs were performed in a 96-well format on a Veriti thermal cycler (Life technology, Carlsbad, CA, USA) using 2x KAPA HiFi Hotstart ReadyMix (KAPA Biosystem, Wilmington, MA, USA). AMPure XP beads (Beckman Coulter, Danvers, MA, USA) were used to purify the V3/ V4 fragment amplicon from free primers and other contaminants.…”
Section: In Vivo Mouse Feeding Trialmentioning
confidence: 99%